Особенности морфологии фрактальных нанообъектов в кристаллах A2VB3VI - Aliyeva, A. P.; Kahramanov, K. Sh.; Kahramanov, S. Sh. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
On interlayer surfaces of crystals of Bi2Te3<impurity> and Sb2Te3<impurity> as a result of self-organisation are formed nano formations of following types: the pyramidal inclusions, parallel plates and the fragments similar Koch fractal surface. The revealed morphological features in A2VB3VI <impurity> crystals connected with formation of interlayers of various thickness can play a basic role in anomalies of electronic properties.